Fringe patterns generated by micro-optical sensors for pattern recognition - Kreangsak Tamee; Khomyuth Chaiwong; Kriengsak Yothapakdee; Preecha P. Yupapin (My University, 2014)
We present a new result of pattern recognition generation scheme using a small-scale optical muscle sensing system, which consisted of an optical add-drop filter incorporating two nonlinear optical side ring resonators. When light from laser source enters into the system, the device is stimulated by an external physical parameter that introduces a change in the phase of light propagation within the sensing device, which can be formed by the interference fringe patterns. Results obtained have shown that the fringe patterns can be used to form the relationship between signal patterns and fringe pattern recognitions.
Keywords: SIGNAL (programming language); Advanced Fiber Optic Sensors